Implementation of Strengthened Technical Vocational Education Program - Competency Based Curriculum, Northern Mindanao, Philippines - Alferez, Reynilda C.; Palmes, Nenita D. (JPAIR Multidisciplinary Research, 2012)
This study attempted to assess the implementation of the Strengthened Technical and Vocational Education Program - Competency Based Curriculum (STVEP-CBC) in Region x. The study involved nine (9) DepED Technical Vocational High Schools in Region X - Northern Mindanao. The respondents included twenty one (21) administrators and ninety one (91) teachers. Descriptive statistics were used to describe and to analyze the data. The study also utilized T - test for paired values to evaluate the difference between administrators and teachers assessments in the status of implementation of STVEP - CBC. The school administrators and teachers assessed the status of the implementation of STVEP-CBC along the aspects of its program. Findings show that both administrators and teacher respondents were assessed very satisfactory on items of Competency Assessment and Certification, Instructional and Teacher Support Material, Curriculum Instruction, Program and Project Management and Monitoring and Evaluation. On one hand, both respondents register as only satisfactory on the aspect of facilities and services. This can be due to the fact that a budgetary allocation in this area is insufficient. On the other hand, assessments of administrators and teachers vary on the following: excellent by the administrators while very satisfactory by the teachers respectively the items on Human Resource Development, Property Supply Management, Fiscal Management and Physical Plant Facility. Such high assessments of the two groups are attributed to their satisfaction level with the implementation of the different programs.